PEER INFLUENCE AND MOOD AS PREDICTORS OF ACADEMIC PERFORMANCE IN HIGH SCHOOL STUDENTS - Kurniawan, Luky; Sholikah, Fitria Akbar (Counsenesia Indonesian Journal Of Guidance and Counseling, 2025)
Student academic performance is not only determined by cognitive abilities, but also influenced by social and emotional factors. One such factor is the influence of peers and the mood experienced by students during the learning process. This study aims to determine the influence of peer influence and mood on academic performance. The study uses a quantitative approach with a correlational method. The sample consisted of 258 students selected through simple random sampling from a population of 719 students. The instruments used were the peer influence scale, mood scale, and academic performance scale, which were developed based on theoretical indicators and validated through expert judgment. The reliability of the instruments was tested using Cronbach's Alpha coefficient, with results of 0.887 for peer influence, 0.927 for mood, and 0.890 for academic performance, indicating high reliability. The data analysis techniques used were multiple linear regression, t-test, and F-test. The research results showed that peer influence had a positive and significant effect on academic performance, while mood had a negative and significant effect. Simultaneously, both variables contributed 54% to academic performance. Thus, it can be concluded that the positive influence of peers contributes to improving students' academic performance, while negative moods have the potential to decrease academic performance.